Komunikasi Asertif pada Mahasiswa Duck Syndrome di Mojokerto - Ratnaningrum Zusyana Dewi (PAWITRA KOMUNIKA : Jurnal Komunikasi dan Sosial Humaniora, 2021)
Often we are forced by the environment to always be adaptive and responsive to various situations. Situations full of pressure, competition, and conflict, make someone must act to immediately find a solution. In the world of students, things like that often cause a dilemma of its own. The academic world and the social world are 2 things that students face every day. In addition to stuttering in dealing with lecture materials that are completely different from their high school years, they also have to experience problems in social relations that are no less complicated. Situations like this cause many students to get duck syndrome, which is a condition where someone looks fine, even though they are struggling as hard as possible to overcome the various problems they are facing. This term is taken from the analogy of a duck in a river that swims gracefully to and fro, even though its feet under the surface of the water are constantly moving to keep its body balanced so it doesn't sink. Students who have just come out of high school face completely new academic and social problems in their campus environment. They try their best to solve problems without being seen in their appearance. Ups and downs are done so that the problems that surround them are quickly resolved. Their performance is still cheerful, happy, and problem-free. If things like this are left alone, it is feared that their performance will not be optimal. They are haunted by constant anxiety, maintain unconscious barriers, and do not find a solution to the problem. With the descriptive method, an overview of how this syndrome affects many students is generated. They are confused about the situation and conditions in their environment. There are some students who can get up and introspect, then look for solutions by communicating their shortcomings and mistakes. But there are also some who still stutter and fail to cope with their academic and social life. Assertive communication offers a solution. Assertive communication is a communication process that dares to express ideas, ideas, criticism, without hurting or demeaning others. This style of communication is usually ideal for dealing with any kind of situation. But apparently not all students can take advantage of it. The ability of students to manage anxiety is different. It is hoped that with assertive communication students can solve the problems they face, so that they do not affect their achievements in the future